Ion and substrate effects on thin film deposition and substrate-radical interactions in RF plasmas - Butoi, Carmen I., author; Fisher, Ellen R., advisor (Colorado State University. Libraries, 2000)
Fluorocarbon plasmas (FCP's) have applications such as generation of interlevel dielectric films and etching in the microelectronics industry, as well as production of biocompatible materials. Ammonia glow discharges are equally useful with applications nitride passivation for integrated circuit manufacture along with polymer surface modification. This work aims to elucidate the underlying chemical mechanisms that control substrate modification in the two plasma systems. The research performed to achieve this goal combines substrate modification and plasma molecular beam studies. The structure and composition of fluorocarbon materials deposited in pulsed and continuous wave (CW) hexafluoropropylene oxide (HFPO) plasmas were investigated. Results indicate a substantial dependence on substrate position relative to the rf coil. When the substrate was placed 8 cm downstream from the rf coil (25 W CW), highly amorphous, cross-linked films were obtained. In contrast, materials deposited further downstream at 28 cm contained less cross-linked moieties and a higher degree of order. Difluorocarbene radicals are believed to play a key role in FCP substrate modification. The surface scatter coefficients, S, of CF2 radicals were determined during plasma processing of substrates using the imaging of radicals interacting with surfaces (IRIS) technique. The plasma molecular beam sources were 100% C2F6, 50/50 C2F6/H2, and 100% HFPO. CW and pulsed glow discharges were investigated. Rf power and substrate material effects on difluorocarbene reactivity were studied along with ion bombardment effects. The radical-surface interaction data were correlated with data from surface characterization of plasma processed substrates. The key finding is that the surface reactivity of CF2 radicals is a good indicator of the overall plasma process: etching or deposition. The interactions of NH2 radicals with different substrate materials during NH3 plasma processing were also investigated using the IRIS technique. For most conditions, S > I, indicating that NH2 generation occurs at the plasma-substrate interface. To obtain information on energy transfer between plasma species and the substrate surface during processing, the translational temperature, ϴTsc, of scattered NH2 molecules was determined under different experimental conditions. The correlation of NH2 scatter coefficients and translational temperature results permitted the identification of the processes most likely involved in NH2 radical surface generation.
Keywords: chemistry; physical chemistry